ANALISIS VEGETASI DI KAWASAN HUTAN DANAU BUYAN TAMBLINGAN BALI SEBAGAI DASAR UNTUK MANAJEMEN KELESTARIAN KAWASAN - Sutomo Sutomo; I Dewa Putu Darma (Environmental Research Center (PPLH) of Udayana University, 2011)
Vegetation analysis in Buyan-Tamblingan Nature Recreation Area aimed to identified whether there were differences between the two communities in terms of vegetation structure and composition. NMDS ordination revealed data that support the hypotheses that the two communities were different (RANOSIM=0.7 p<0,001). Species diversity was also different between these communities. Buyan area had higher diversity index (Shannon 2,00) compare to Tamblingan (1,60). Differences in tourism activities and impacts were proposed to be one of the reason behind the results. Restoration in a form of reintroduction, to reintroduce and re-planting native or local species is proposed to be conducted in the Buyan Lake areas to conserve the ecosystem and prevent exotic species to become invasives and dominates the area.